Pengamanan Data Finansial Menggunakan Enkripsi Homomorfik Pailler - Sukmana, Ida Bagus Made Wiguna Tedja; Muliantara, Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 2 (2025): JNATIA Vol. 3, No. 2, Februari 2025DO - 10.24843/JNATIA.2025.v03.i02.p04, 2025)
In the current digital era, concerns about data privacy are increasing due to the ease of data creation, storage, access, and dissemination. To protect sensitive data, such as financial information and identities, effective methods are needed to safeguard privacy from unauthorized access. One such method is homomorphic encryption, which allows computations to be performed on encrypted data without the need for decryption. This research implements the Paillier Cryptosystem in financial data security, specifically for customer savings accounts. The encryption and computation processes on savings data are performed using homomorphic encryption, ensuring data confidentiality and customer privacy. The testing results demonstrate that the system can perform homomorphic computations effectively, producing results consistent with plaintext calculations. In conclusion, the use of homomorphic encryption in financial data security can enhance privacy, security, and data reliability while providing more control to data owners.